I love you, baby burrito - Dominguez, Angela (Roaring Brook Press, 2021)
"From Pura Belpre honoree Angela Dominguez, Love You Baby Burrito is a modern classic picture book celebrating the act of swaddling a newborn into a baby burrito."--Provided by publisher